Cmp polishing pad with enhanced polishing rate

JP2022159069A5Active Publication Date: 2025-03-19DUPONT ELECTRONIC MATERIALS HLDG INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022049560
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-03-31
Filing Date
2022-03-25
Publication Date
2025-03-19
Estimated Expiration
2042-03-25

AI Technical Summary

Technical Problem

Conventional chemical mechanical polishing (CMP) processes for semiconductor substrates have slow removal rates, particularly in high-capacity multi-layer memory devices like 3D NAND flash memory, leading to long processing times without a significant increase in defects.

Method used

A polishing pad comprising a polymeric matrix with rate-enhancing layered particles, such as zirconium hydrogen phosphate, which are positively charged at acidic pH, improving abrasive performance and reducing substrate defects.

Benefits of technology

The polishing pad significantly enhances removal rates by up to 20% while reducing defects by up to 50%, particularly effective in ceria-based slurries, and maintains efficient polishing in various slurry conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide means of improving, preferably without increasing defects, a removal rate important to efficiency of a process of making an electronic device.SOLUTION: In chemical mechanical polishing, a polishing pad having a polishing portion comprising a polymer matrix and rate enhancing lamellar particles that include a phosphate or arsenate of a group III-A or IV-A metal can be effective in chemical mechanical polishing especially when using slurry comprising particles having a positive charge in slurry conditions.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] Field of Invention The present invention relates to polishing pads for chemical-mechanical polishing of substrates, including, in general, polishing using ceria-based slurries, particularly during the formation of premetallic insulating films.

[0002] background In the assembly of integrated circuits and other electronic devices, multiple layers of conductive, semiconductor, and insulating materials are deposited on the surface of a semiconductor wafer and partially or selectively removed from the surface. Thin layers of conductive, semiconductor, and insulating materials can be deposited using several deposition techniques. In the damascene process, material is deposited to fill depressions created by patterned etching of trenches and vias. Since the filling is conformal, this can result in irregular surface topography. Also, excess material can be deposited to avoid underfilling. Therefore, it is necessary to remove the material outside the recesses. Common deposition techniques in modern wafer processing include, among others, physical vapor deposition (PVD), also known as sputtering, chemical vapor deposition (CVD), plasma-enhanced chemical vapor deposition (PECVD), and electrochemical deposition (ECD). Common removal techniques include, among others, wet and dry etching; isotropic and anisotropic etching.

[0003] As materials are continuously deposited and removed, the substrate topography can become non-uniform or non-planar. Subsequent semiconductor processing (e.g., photolithography, metallization) requires the wafer to have a flat surface, thus necessitating wafer planarization. Planarization is useful for removing undesirable surface topography and surface defects such as rough surfaces, aggregated materials, crystal lattice damage, scratches, and contaminated layers or materials.

[0004] Chemical mechanical planarization, also known as chemical mechanical polishing (CMP), is a common technique used in damascene processes, front-end-of-line (FEOL) processing, or back-end-of-line (BEOL) processing to planarize or polish workpieces such as semiconductor wafers to remove excess material. In conventional CMP, a wafer carrier, or polishing head, is mounted on a carrier assembly. The polishing head holds the wafer and positions it so that it is in contact with the polishing surface of a polishing pad mounted on a table or platen within the CMP apparatus. The carrier assembly provides controllable pressure between the wafer and the polishing pad. Simultaneously, a slurry or other polishing medium is dispensed onto the polishing pad and drawn into the gap between the wafer and the polishing layer. To perform polishing, the polishing pad and wafer typically rotate relative to each other. As the polishing pad rotates beneath the wafer, the wafer generally sweeps up an annular polishing track, or polishing area, in which the wafer surface directly faces the polishing layer. The wafer surface is polished and planarized by the chemical and mechanical action of the polishing surface and the polishing medium (e.g., slurry) on the surface.

[0005] The removal rate is crucial for the efficiency of the process of fabricating electronic devices. For example, in high-capacity multilayer memory elements (e.g., 3D NAND flash memory), the manufacturing process may involve assembling multilayer stacks of SiO2 and Si3N4 films alternately in a pyramidal, staircase-like structure. Once completed, the stack is capped with a thick SiO2 coating layer, which must be planarized before the device structure is complete. The device capacitance is proportional to the number of layers in the stacked structure. Commercially available devices generally use 32 and 64 layers, and the industry is rapidly progressing towards 128 layers. The thickness of each oxide / nitride pair in the stack is approximately 125 nm. Therefore, the thickness of the stack increases in direct proportion to the number of layers (32 layers have a thickness of approximately 4,000 nm, 64 layers have a thickness of approximately 8,000 nm, and 128 layers have a thickness of approximately 16,000 nm). The total amount of capping insulator to be removed can be approximately 1.5 times the thickness of the stack (e.g., up to approximately 24,000 nm). Conventional insulator CMP slurries have a removal rate of approximately 250 nm / min, resulting in unnecessarily long CMP process times, which can be a barrier in 3D NAND manufacturing processes. Many efforts to develop faster CMP processes have focused on process conditions, such as higher pressure, faster contact speed, pad conditioning, and slurry composition. However, improving the removal rate cannot be done without sacrificing an increase in defects in the polished substrate. Therefore, there is a need for means to improve the removal rate, preferably without increasing defects.

[0006] Summary of the Invention In this specification, a polishing pad useful in chemical mechanical polishing is provided, having an abrasive comprising a polymer matrix material and layered particles for improving the polishing rate, wherein the layered particles are hydrogen phosphates or hydrogen arsenates of group III-A or group IV-A metals, preferably of formula: M(HYO4)2n(H2O) [In the formula, M is a metal ion of Group III-A or Group IV-A, preferably Zr +4 Ti +4 or Ce+4 , most preferably Zr +4 A polishing pad is disclosed comprising a metal hydrogen phosphate or metal hydrogen arsenate, where Y is P or As, preferably P, and n is 0, 1 or 2, preferably 1.

[0007] Furthermore, this specification also discloses a method comprising the steps of providing a substrate, providing a polishing pad as described in claim 1, providing a slurry between the polishing pad and the substrate, and polishing the substrate using the pad and the slurry, wherein the polishing is carried out at a pH in which the slurry contains particles having a generally positive surface charge in an aqueous medium such as deionized water. For the purposes of this specification, a positive surface charge means that the pH of the polishing slurry is below its isoelectric point. [Brief explanation of the drawing]

[0008] [Figure 1] Figure 1 is a schematic diagram showing the chemical structure of an example of a rate-enhancing layered particle additive disclosed herein.

[0009] Detailed description of the invention This specification discloses a polishing pad having a polishing portion comprising a polymer matrix and rate-enhancing layered particles.

[0010] The rate-improving layered particles can be metal hydrogen phosphates or metal hydrogen arsenates. The rate-improving layered particles can have a laminated structure. Although not desiring to be restricted, the laminated structure is assumed to be able to reduce the possibility of damaging the substrate to be polished by large particles and causing defects. The rate-improving layered particles can have a plate-like structure (especially, a laminated plate-like structure). The average dimension in the major axis direction of the particles (i.e., the length and / or width substantially perpendicular to the thickness) can be at least 0.5, or at least 1 micron, or at least 2 microns, and at the same time, can be at most 20, or at most 10, or at most 5 microns. The particles can have an aspect ratio (length or width: thickness) of 3 to 20 or 3 to 10.

[0011] The rate-improving layered particles can have a crystal structure. FIG. 1 illustrates an example of the molecular structure of such layered particles, showing zirconium (as the metal) and phosphate groups. Each layer can have a plane of metal ions, and hydrogen phosphate (or arsenate) groups are bonded (e.g., cross-linked) above and below the plane of the metal ions. The outer surface of the layer where hydrogen phosphate (or arsenate) is cross-linked can be terminated with P-OH groups (or As-OH groups). The metal ions (Zr +4 is shown) can be bonded on either side of a phosphate group or an arsenate group (a phosphate group is shown) to form an alternating structure or a layered structure. Water can be bonded to the hydroxyl groups. The metal ions can be metal ions of Group III-A or Group IV-A, for example, zirconium ions (e.g., Zr +4 ), titanium ions (e.g., Ti +4 ), or cerium ions (e.g., Ce +4 ).

[0012] The particles can be metal ions (e.g., Zr +4The particles can typically have several layers to which phosphate groups (or arsenic groups) are bonded in the form of metal oxides. At pH levels above isoelectric pH (approximately 3 for zirconium hydrogen phosphate) in aqueous solutions, the surface is strongly negative due to the numerous surface hydroxyl groups. The particles are also hydrophilic but chemically inert and insoluble in water. The particles can be highly fragile, thus reducing the likelihood of scratch defects during polishing with larger particles. Furthermore, these particles can cleave to form plates, which can improve polishing performance by increasing the removal rate, among other things.

[0013] Metal phosphates or metal arsenates are given by the formula: M(HYO4)2n(H2O) [In the formula, M is a metal ion of Group III-A or Group IV-A, preferably Zr +4 Ti +4 or Ce +4 , most preferably Zr +4 Y can be P or As, preferably P, and n can be 0, 1 or 2, preferably 1.

[0014] The amount of rate-improving layered particles disclosed herein used in the abrasive portion of the pad may range from at least 0.1, or at least 1, or at least 2, or at least 3, or at least 5, based on the total weight of the abrasive portion, to a maximum of 20, or at least 15, or at least 10 weight percent. The amount of rate-improving layered particles may range from 0.1 to 20 volume percent, or 1 to 18 volume percent, or 2 to 15 volume percent, based on the total volume of the abrasive portion.

[0015] The polishing portion may include any polymer base material commonly used in polishing pads. The polishing portion may include thermoplastic polymers or thermosetting polymers. Examples of polymers that can be used in the polishing portion among polymer materials that can be used in the base pad or polishing portion include polycarbonate, polysulfone, nylon, epoxy resin, polyether, polyester, polystyrene, acrylic polymer, polymethyl methacrylate, polyvinyl chloride, polyvinyl fluoride, polyethylene, polypropylene, polybutadiene, polyethyleneimine, polyurethane, polyethersulfone, polyamide, polyetherimide, polyketone, epoxy, silicone, copolymers thereof (such as polyether-polyester copolymers), and combinations or formulations thereof. The polymer may be polyurethane.

[0016] The polishing section may have a Young's modulus (according to ASTM D412-16) of at least 2, at least 2.5, at least 5, at least 10, or at least 50 MPa, up to 900, up to 700, up to 600, up to 500, up to 400, up to 300, or up to 200 MPa. The polishing section may be opaque to the signal used for endpoint detection.

[0017] The abrasive portion can also include other particles, such as, in particular, hollow micro-elements, especially flexible hollow polymer micro-elements (e.g., microspheres). For example, a plurality of micro-elements can be uniformly dispersed throughout the abrasive layer. The plurality of micro-elements can simply be pores (e.g., enclosed gas bubbles) in the base material, or can be a hollow core polymer material, a liquid-filled hollow core polymer material, a water-soluble material or an insoluble phase material (e.g., mineral oil). The plurality of micro-elements, for example, provide porosity to the abrasive element when the micro-elements are selected from enclosed gas bubbles and hollow core polymer materials that are uniformly distributed throughout the abrasive layer. The micro-elements can have a weight average diameter of up to 150 microns or up to 50 microns while having a diameter of at least 10 microns. The weight average diameter can be measured using laser diffraction, such as low angle laser light scattering (LALLS). The plurality of micro-elements can include polymer microballoons (e.g., Expancel® microspheres manufactured by Akzo Nobel) having a shell wall of either polyacrylonitrile or a polyacrylonitrile copolymer. The plurality of micro-elements can be incorporated into the abrasive layer in an amount from 0, or at least 5 or at least 10 volume percent, up to 50, 45, 40, or 35 volume percent. When the micro-elements provide porosity, the porosity of the abrasive portion can be a porosity of 0 to 50, 5 to 45 or 10 to 35 volume percent. The volume percent of porosity can be determined by dividing the difference in specific gravity between the unfilled abrasive layer and the abrasive layer containing the micro-elements by the specific gravity of the unfilled abrasive layer. Alternatively, the percent porosity can also be determined by dividing the density of the abrasive layer by the weighted average density of the non-filled components of the abrasive layer. Metal phosphates are particularly useful for machining non-porous abrasive pads. For example, metal phosphate particles can improve the machining of grooves from a lathe operating with a fixed cutting tool or grooving with a spinning tool bit.

[0018] The abrasive portion has a density of 0.4 to 1.15, or 0.7 to 1.0 g / cm when measured in accordance with ASTM D1622 (2014). 3It can have a density of

[0019] The polishing portion can have a Shore D hardness of 28 to 75 when measured in accordance with ASTM D2240 (2015).

[0020] The polishing portion can have an average thickness of 20 to 150 mils, 30 to 125 mils, 40 to 120 mils, or 50 to 100 mils (0.5 to 4, 0.7 to 3, 1 to 3, or 1.3 to 2.5 mm).

[0021] The polishing pad of the present invention optionally further includes at least one additional layer in surface contact with the polishing layer. For example, the polishing pad can further include a crimpable base layer that adheres to the polishing layer. The crimpable base layer preferably improves the compatibility of the polishing layer with the surface of the substrate to be polished. The base pad (also referred to as a sub-layer or base layer) can be used under the polishing portion. The base pad can be a single layer or can include multiple layers. The upper surface of the base pad can be defined as a plane in x-y orthogonal coordinates. For example, the polishing portion can be adhered to the base pad via a mechanical fastener or by an adhesive. The base layer can have a thickness of at least 0.5 mm or at least 1 mm. The base layer can have a thickness of 5 mm or less, 3 mm or less, or 2 mm or less.

[0022] The base pad or base layer may contain any material known for use as a base layer for an abrasive pad. For example, the base pad or base layer may include polymers, polymer formulations, or composites of polymer materials with other materials, such as ceramics, glass, metals, or stone. Polymers and polymer composites can be used as base pads, particularly as upper layers when there are multiple layers, for reasons of compatibility with the material that can form the abrasive surface. Examples of such composites include polymers filled with carbon or inorganic fillers, and polymer-impregnated fiber mats (e.g., of glass or carbon fiber). The base of the pad may be made of a material having one or more of the following properties: Young's modulus in the range of 900, 700, 600, 500, 400, 300, or 200 MPa, from at least 2, at least 2.5, at least 5, at least 10, or at least 50 MPa (e.g., as determined by ASTM D412-16); Poisson's ratio of 0.6 or 0.5, from at least 0.05, at least 0.08, or at least 0.1, from at least 0.6, or at least 0.5, from at least 0.4, or at least 0.5, from at least 1.7, 1.5, or at least 1.3 grams / cm³ (g / cm³). 3 The density of )

[0023] Examples of such polymer materials that can be used in the base pad or polishing section include polycarbonate, polysulfone, nylon, epoxy resin, polyether, polyester, polystyrene, acrylic polymer, polymethyl methacrylate, polyvinyl chloride, polyvinyl fluoride, polyethylene, polypropylene, polybutadiene, polyethyleneimine, polyurethane, polyethersulfone, polyamide, polyetherimide, polyketone, epoxy, ethylene-vinyl acetate (EVA or PEVA), ethylene propylene diene monomer rubber (EPDM rubber), silicone, copolymers thereof (such as polyether-polyester copolymer), or combinations or formulations thereof.

[0024] The polymer can be polyurethane. Polyurethane may be used alone or as a base material for carbon or inorganic fillers and fiber mats (e.g., glass or carbon fiber).

[0025] For the purposes of this specification, “polyurethane” refers to products obtained from bifunctional or polyfunctional isocyanates, such as polyetherureas, polyisocyanurates, polyurethanes, polyureas, polyurethane ureas, copolymers thereof, and mixtures thereof. Therefore, CMP polishing pads may be manufactured by a method comprising the steps of: providing an isocyanate-terminated polyurethane prepolymer; separately providing a curable component; and combining the isocyanate-terminated polyurethane prepolymer and the curable component to form a composite, and reacting the composite to form a product. A base pad or base layer can be formed by skiving a molded polyurethane cake to a desired thickness. Optionally, preheating the cake mold with IR irradiation, induction, or DC current can reduce product variation when molding a porous polyurethane matrix. Optionally, either a thermoplastic polymer or a thermosetting polymer can be used. The polymer may be a crosslinked thermosetting polymer.

[0026] When polyurethane is used in the base pad and / or polishing layer, the polyurethane can be a reaction product of a polyfunctional isocyanate and a polyol. For example, a polyisocyanate-terminated urethane prepolymer can be used. The polyfunctional isocyanate used in forming the polishing layer of the chemical mechanical polishing pad of the present invention can be selected from the group consisting of aliphatic polyfunctional isocyanates, aromatic polyfunctional isocyanates, and mixtures thereof. For example, the polyfunctional isocyanate used in forming the polishing layer of the chemical mechanical polishing pad of the present invention may be a diisocyanate selected from the group consisting of 2,4-toluene diisocyanate; 2,6-toluene diisocyanate; 4,4'-diphenylmethane diisocyanate; naphthalene-1,5-diisocyanate; tolidine diisocyanate; para-phenylenedi diisocyanate; xylylene diisocyanate; isophorone diisocyanate; hexamethylene diisocyanate; 4,4'-dicyclohexylmethane diisocyanate; cyclohexane diisocyanate; and mixtures thereof. The polyfunctional isocyanate may be an isocyanate-terminated urethane prepolymer formed by the reaction of a diisocyanate with a prepolymer polyol. Isocyanate-terminated urethane prepolymers may have 2-12 wt%, 2-10 wt%, 4-8 wt%, or 5-7 wt% unreacted isocyanate (NCO) groups. The prepolymer polyol used to form the polyfunctional isocyanate-terminated urethane prepolymer can be selected from the group consisting of diols, polyols, polyoldiols, copolymers thereof, and mixtures thereof.For example, the prepolymer polyol can be selected from the group consisting of polyether polyols (e.g., poly(oxytetramethylene) glycol, poly(oxypropylene) glycol, and mixtures thereof); polycarbonate polyols; polyester polyols; polycaprolactone polyols; mixtures thereof; and mixtures thereof with one or more low molecular weight polyols selected from the group consisting of ethylene glycol; 1,2-propylene glycol; 1,3-propylene glycol; 1,2-butanediol; 1,3-butanediol; 2-methyl-1,3-propanediol; 1,4-butanediol; neopentyl glycol; 1,5-pentanediol; 3-methyl-1,5-pentanediol; 1,6-hexanediol; diethylene glycol; dipropylene glycol; and tripropylene glycol. For example, the prepolymer polyol can be selected from the group consisting of polytetramethylene ether glycol (PTMEG); ester polyols (such as ethylene adipate and butylene adipate); polypropylene ether glycol (PPG); polycaprolactone polyols; copolymers thereof; and mixtures thereof. For example, the prepolymer polyol can be selected from the group consisting of PTMEG and PPG. When the prepolymer polyol is PTMEG, the isocyanate-terminated urethane prepolymer can have an unreacted isocyanate (NCO) concentration of 4 to 12 wt% (more preferably 6 to 10 wt%; most preferably 8 to 10 wt%).Examples of commercially available PTMEG-based isocyanate-terminated urethane prepolymers include Imuthane® prepolymer (available from COIM USA, Inc., e.g., PET 80A, PET 85A, PET 90A, PET 93A, PET 95A, PET 60D, PET 70D, PET 75D); Adiprene® prepolymer (available from Chemtura, e.g., LF 800A, LF 900A, LF 910A, LF 930A, LF 931A, LF 939A, LF 950A, LF 952A, LF 600D, LF 601D, LF 650D, LF 667, LF 700D, LF750D, LF751D, LF752D, LF753D and L325); and Andur® prepolymer (Anderson Development Available from the Company, for example, 70APLF, 80APLF, 85APLF, 90APLF, 95APLF, 60DPLF, 70APLF, 75APLF). When the prepolymer polyol is PPG, the isocyanate-terminated urethane prepolymer can have an unreacted isocyanate (NCO) concentration of 3-9 wt% (more preferably 4-8 wt%, most preferably 5-6 wt%). Examples of commercially available PPG-based isocyanate-terminated urethane prepolymers include Imuthane® prepolymers (available from COIM USA, Inc., e.g., PPT 80A, PPT 90A, PPT 95A, PPT 65D, PPT 75D); Adiprene® prepolymers (available from Lanxess, e.g., LFG 963A, LFG 964A, LFG 740D); and Andur® prepolymers (available from Anderson Development Company, e.g., 8000APLF, 9500APLF, 6500DPLF, 7501DPLF). The isocyanate-terminated urethane prepolymers can be low-free isocyanate-terminated urethane prepolymers having a free toluene diisocyanate (TDI) monomer content of less than 0.1 wt%. Non-TDI-based isocyanate-terminated urethane prepolymers can also be used.For example, isocyanate-terminated urethane prepolymers can be formed by the reaction of 4,4'-diphenylmethane diisocyanate (MDI) with a polyol such as polytetramethylene glycol (PTMEG), but any diol such as 1,4-butanediol (BDO) is acceptable. When such an isocyanate-terminated urethane prepolymer is used, the concentration of unreacted isocyanate (NCO) is preferably 3 to 10 wt% (more preferably 4 to 10 wt%, most preferably 5 to 10 wt%). Examples of commercially available isocyanate-terminated urethane prepolymers in this category include Imuthane® prepolymers (available from COIM USA, Inc., e.g., 27 85A, 27 90A, 27 95A); Andur® prepolymers (available from Anderson Development Company, e.g., IE75AP, IE80AP, IE85AP, IE90AP, IE95AP, IE98AP); and Vibrathane® prepolymers (available from Chemtura, e.g., B625, B635, B821).

[0027] The final form of the polishing pad of the present invention may further include the incorporation of one-dimensional or multi-dimensional textures on its upper surface. These may be classified as macrotextures or microtextures depending on their size. Common types of macrotextures used in CMP for controlling hydrodynamic reactions and / or slurry transport include, but are not limited to, grooves of many configurations and designs, such as annular, radial, and cross-hatching. These may be formed on a thin, uniform sheet via machining or directly on the pad surface via net-shape forming. Common types of microtextures are fine-scale shapes that create surface irregularities that are contact points with the substrate wafer being polished. Common types of microtextures include, but are not limited to, textures formed before, during, or after use by abrasion with many hard particles such as diamond (often referred to as pad conditioning), and microtextures formed during the pad manufacturing process.

[0028] The polishing pad of the present invention is adaptable to make surface contact with the platen of a chemical mechanical polishing machine. The polishing pad can be fixed to the platen of the polishing machine. The polishing pad can be fixed to the platen using at least one of a pressure-sensitive adhesive and a vacuum.

[0029] The CMP pads of the present invention can be manufactured by a wide variety of processes that are compatible with the properties of the pad polymer used. These include mixing the components described above, pouring them into a mold, annealing them, and slicing them into sheets of the desired thickness. Alternatively, they may be manufactured by more precise net-shape molding. Manufacturing processes include: 1. thermosetting injection molding (often referred to as “reaction injection molding” or “RIM”), 2. thermoplastic or thermosetting injection blow molding, 3. compression molding, or 4. any similar type of process in which a fluid material is placed and solidified to create at least part of the macro-texture or micro-texture of the pad. In an example of molding a polishing pad: 1. a fluid material is delivered into or onto a structure or substrate; 2. as the material solidifies, the structure or substrate may impart a surface texture to the material; and 3. the structure or substrate is subsequently separated from the solidified material.

[0030] method The polishing pads disclosed herein can be used to polish substrates. For example, a polishing method may include the steps of providing a substrate to be polished, and then polishing it using the pads disclosed herein. The substrate can be any substrate to which polishing and / or planarization is desired. Examples of such substrates include magnetic substrates, optical substrates, and semiconductor substrates. A specific example is a premetal insulating film stack. The specific material to be polished on the substrate may be a silicon oxide layer. The method can be part of a front-end-of-line or back-end-of-line processing for an integrated circuit. For example, this process can be used to remove undesirable surface topography and surface defects such as rough surfaces, aggregated materials, crystal lattice damage, scratches, and contaminated layers or materials. In addition, in a damascene process, material is deposited to fill depressions created by one or more steps of photolithography, patterned etching, and metallization. Certain steps may be inaccurate, for example, overfilling of recesses may occur. The method disclosed herein can be used to remove material outside of recesses. This process can be chemical-mechanical planarization or chemical-mechanical polishing, both of which may be referred to as CMP. A carrier can hold the substrate to be polished, for example, a semiconductor wafer (with or without layers formed by lithography and metallization) that comes into contact with the polishing elements of the polishing pad. A slurry or other polishing medium can be dispensed into the gap between the substrate and the polishing pad. The polishing pad and the substrate move relative to each other, for example, by rotating. The polishing pad is typically placed beneath the substrate to be polished. The polishing pad can rotate. The substrate to be polished can also move, for example, on a polishing track (e.g., annular). Through relative movement, the polishing pad approaches and contacts the surface of the substrate.

[0031] The pads disclosed herein can be used with any slurry. The inventors have found that using the pads disclosed herein with a slurry having positively charged (or positively surface-charged) particles during polishing conditions can provide a significant improvement in removal rate. Although we do not wish to be constrained, it is assumed that rate-enhancing layered particles can provide a pad surface having a relatively high concentration of anionic hydroxyl moieties to which positively charged particles present during polishing can bind.

[0032] The platen pressure can be 1–5, 1.5–4.5, or 2–4 pounds per square inch (psi) (approximately 6–35, 10–30, or 13–28 kilopascals (kPa)). The platen speed can be approximately 40–150, or 50–130 rpm. The amount of slurry added can be, for example, 50–500 milliliters / minute. The pH of the slurry during grinding can be as low as 2, 2.5, or 3, from a maximum of 7, or a maximum of 6.8.

[0033] For example, the benefit of improved removal rate is particularly pronounced in ceria-based slurries. In ceria-based slurries, particles can have a positive charge (or positive surface charge) at a pH of about 6.5 or less due to CeO2, and such a ceria-based slurry may contain ceria particles ranging from at least 0.01 or at least 0.1 weight percent to a maximum of 20, or a maximum of 15, or a maximum of 10, or a maximum of 5, or a maximum of 2 weight percent based on the total weight of the slurry. The ceria-based slurry may contain ceria alone as single particles, or it may contain additional other particles. These other particles may be, for example, other particles that have a positive (surface) charge at the pH in which polishing is performed. The other particles may be, for example, silica particles or alumina particles, preferably silica particles or alumina particles that have a positive surface charge at the pH in which polishing is performed. The improvement in removal rate can also be observed in certain silica-based slurries, in particular silica-based slurries having particles that have a positive (surface) charge at the pH in which polishing is performed.

[0034] For example, the method may include the steps of: providing a chemical-mechanical polishing apparatus having a platen or carrier assembly; providing at least one substrate to be polished; providing a chemical-mechanical polishing pad disclosed herein; mounting the chemical-mechanical polishing pad on a platen; optionally, providing a polishing medium (e.g., a slurry containing abrasive particles and / or a reactive liquid composition not containing abrasive particles) at the interface between the polishing portion of the chemical-mechanical polishing pad and the substrate; and creating dynamic contact between the polishing portion of the polishing pad and the substrate so that at least some of the material is removed from the substrate. The carrier assembly can provide controllable pressure between the substrate to be polished (e.g., a wafer) and the polishing pad. The polishing medium can be dispensed onto the polishing pad and drawn into the gap between the wafer and the polishing layer. The polishing medium may include water, a pH adjuster, and optionally, but not limited to, one or more of the following: abrasive particles, oxidizing agents, inhibitors, biocides, soluble polymers, and salts. Abrasive particles can be oxides, metals, ceramics, or other appropriately hard materials. Typical abrasive particles include colloidal silica, fumed silica, ceria, and alumina. The polishing pad and substrate can rotate relative to each other. As the polishing pad rotates under the substrate, the substrate can sweep out a generally annular polishing track, or polishing area, in which the wafer surface directly faces the polishing portion of the polishing pad. The wafer surface is polished and planarized by the chemical and mechanical action of the polishing layer and polishing medium on the surface. Optionally, the polishing surface of the polishing pad can be conditioned with an abrasive conditioner before polishing begins.

[0035] Using pads containing rate-enhancing layered particles as described herein can be particularly effective in improving removal rates while avoiding defects. For example, using a slurry with positively charged particles (e.g., a ceria-based slurry with a pH of up to 7, or up to 6.5, or up to 6) can improve removal rates (e.g., removal rate of tetraethyl orthosilicate (TEOS)) by more than 10 percent, 15 percent, or 20 percent compared to polishing with an equivalent pad lacking rate-enhancing layered particles (e.g., ZHP), while reducing defects by more than 10 percent, 30 percent, or 50 percent.

[0036] Optionally, the pad may include a window for endpoint detection. In that case, the chemical-mechanical polishing apparatus provided in the method of the present invention may further include a signal source (e.g., a light source) and a signal detector (e.g., a photosensor (preferably a multisensor spectrograph)). In that case, the method may further include the step of passing a signal (e.g., light from a light source) through the window and analyzing the signal (e.g., light) reflected from the surface of the substrate and passing in the opposite direction through the endpoint detection window and incident on the sensor (e.g., a photosensor) to determine the polishing endpoint. The substrate may have a metal or metallized surface, for example, containing copper or tungsten. The substrate may be a magnetic substrate, an optical substrate, or a semiconductor substrate. [Examples]

[0037] material PTMEG (polytetramethylene ether glycol) formulation The prepolymer contains 8.95-9.25 wt% H₂O₃. 12 MDI / TDI-PTMEG formulation The brand name for TDI (toluene diisocyanate) is Dow's Voranate T-80 (trademark). H 12 MDI (Alicyclic Diisocyanate) MBOCA(4,4'-methylenebis(2-chloroaniline)) Zirconium hydrogen phosphate powder (ZHP, plate-like with an average particle size of 1-6 microns) ExpanseL (trademark) microporous particles 551DE40d42 manufactured by Nouryon (formerly Akzo Nobel)

[0038] Synthesis of prepolymers The prepolymer can be synthesized in batches (e.g., 200-1000 grams). The PTMEG components are combined to create a polyol mixture. Before adding to the polyol mixture, TDI and H 12 Mix the MDI in an 80:20 ratio. Then, add enough isocyanate mixture to the polyol mixture to achieve the desired NCO weight percentage. Mix the entire mixture again, then leave it in a preheated oven at 65°C for 4 hours before use. All samples were used on the same day as synthesis. Alternatively, prepolymer H 12 Pads can also be fabricated using MDI / TDI-PTMEG formulations directly.

[0039] Pad production The synthesized prepolymer or L-325 is heated to 65°C. Mboca is pre-weighed and melted in an oven at 95°C. ZHP is added to the prepolymer to produce layered particles of varying levels. The ZHP and prepolymer are mechanically mixed. Expansionl® 551DE40d42 microporous particles are then added to the prepolymer and ZHP mixture. The mixture of prepolymer, ZHP, and Expansionl hollow microspheres is thoroughly mixed and degassed using a vacuum. All samples had sufficient Expansion added to reach the desired final density. After degassing, MBOCA is added to the prepolymer, ZHP, and Expansionl mixture and thoroughly mixed. The sample is then poured onto a heating plate and spread using a polytetrafluoroethylene (PTFE) coated bar at 175 mil intervals. The plate is then transferred to an oven and heated to 104°C, where it is maintained for 16 hours. Next, the excess material was removed from the mold, edged, and punched out to a diameter of 22 inches (55.9 cm), which was used to prepare thin, plate-like pads for polishing. All pads were 20 inches (50.8 cm) in diameter, with a top pad thickness of 80 mils (0.2 cm), grooved in a circular pattern (30 mils deep, 20 mils wide, and 120 mils pitch, or 0.76 mm deep, 0.51 mm wide, and 3 mm pitch), and finished with pressure-sensitive adhesive, Suba IV sub-pad, and CR-II platen adhesive. Control pads were prepared using a similar process without ZHP additives. Each material set was also processed into plaques for characterization testing, and characterization was performed both with and without ExpanseL filler.

[0040] Example 1 Polyurethane formulations were prepared with various ZHP addition levels according to the procedure described above. Table 1 shows an overview of the material properties for the three materials. While hardness or modulus (G') remained within the usable range, tensile strength decreased in direct proportion to the amount of ZHP added. The functional limit of the decrease in elongation and toughness without undesirable effects on the polishing process was estimated to occur at a maximum addition weight of approximately 15 weight percent.

[0041] [Table 1]

[0042] Example 2 TEOS wafers were polished using a commercially available CeO2-based slurry (Asahi CES333) with pads containing 10 wt% ZHP and pads without ZHP. The slurry was prepared according to the manufacturer's instructions. The pH of the slurry was 5.5. Based on past data, this pH is well below the isoelectric pH of the particles used, and the particles carry at least some degree of positive charge. A 200 mm TEOS wafer was polished using a single set of process conditions with each pad. The polishing conditions used in each test were a platen speed of 93 rpm, a wafer carrier speed of 87 rpm, and a slurry flow rate of 200 ml / min. The polishing equipment used was an Applied Materials Mirra CMP polishing tool. A significant improvement in polishing rate was observed, with the ZHP-10 pad having a removal rate of 1930 angstroms / min compared to a removal rate of 1604 angstroms / min for the pad without ZHP. Furthermore, a reduction in polishing defects was observed; pads without ZHP had an average of 62 scratch defects per wafer, compared to only 15 in pads with 10 weight percent ZHP. These results demonstrate that the introduction of the hydrogen phosphate layered particles of the present invention into the pads of the present invention was effective in increasing the polishing rate when polishing was performed at a pH in which the particles were at least partially cationized.

[0043] Example 3 TEOS wafers were polished using three commercially available CeO2-based slurries (Hitachi H8005, Versum STI2100F, and Asahi CES333) with pads containing 10 wt% ZHP and pads without ZHP. All slurries were prepared according to the manufacturer's instructions. The pH during use was 5.5. Based on past data, this pH is well below the isoelectric pH of the particles used, and the particles should carry at least some degree of positive charge. A 200 mm TEOS wafer was polished using a single set of process conditions with each pad. The polishing conditions used in each test were a platen speed of 93 rpm, a wafer carrier speed of 87 rpm, and a slurry flow rate of 150 ml / min. The polishing equipment used was an Applied Materials Mirra CMP polishing tool.

[0044] As shown in Table 2, a significant improvement in polishing rate was observed with the pad of the present invention compared to the ZHP-free reference in all test slurries. These results demonstrate that the introduction of hydrogen phosphate additives to the pad of the present invention is effective in increasing the polishing rate for multiple ceria slurry formulations when the pH criteria set forth in the present invention are met.

[0045] [Table 2]

[0046] Furthermore, in three different slurries, the silicon nitride selectivity increased by an average of 12% with the ZHP-10 pad compared to the control pad without ZHP.

[0047] Example 4 TEOS wafers were polished using commercially available CeO2-based slurry (Asahi CES333) and commercially available SiO2-based slurry (Dow K1730) with pads containing 10 wt percent ZHP and pads without ZHP. The slurries were prepared according to the manufacturer's instructions. The CeO2-based slurry had a pH of 5.5 and a solid content of 1 wt% at use. The SiO2 slurry had a pH of 10.5 (this is above the isoelectric pH of the slurry, meaning the particles do not carry a positive charge) and a solid content of 16 wt% at use. Each of the four slurry / pad combinations was polished at two different polishing speeds with various downforces ranging from 1.5 to 4 psi. Multiple TEOS wafers were polished with each of the above combinations, and the coefficient of friction during polishing was measured as well as the removal rate.

[0048] Furthermore, using experimental data on pressure, rate, and velocity, the Preston coefficient k was determined by dividing the polishing rate of each sample by the product of the pressure and velocity of the test. Since the two slurries used had completely different solid content, an additional measure of polishing efficiency could also be determined by dividing k by the solid percentage of each sample being polished. The polishing efficiency of the SiO2-based slurry was the same at 0.5 for both the pad with and without ZHP. The polishing efficiency of the CeO2-based slurry was 4.9 with the pad without ZHP and 6.5 with the pad with ZHP.

[0049] The coefficient of friction (COF) data calculated from the motor torque and slurry temperature of the polishing table provided additional insights into the improvements achieved by the pads of the present invention. As is evident from Table 3, all data for CeO2-based slurries showed significantly higher COF than data for SiO2-based slurries. Furthermore, the COF of pads containing ZHP was significantly higher than that of pads without ZHP. This was evidence that the concentration of CeO2 particles on the pad surface of the ZHP-containing pads was higher due to the presence of metal hydrogen phosphate particles. Similar to the rate, no such effect was observed when using negatively charged particle slurries (e.g., negatively charged SiO2 particles).

[0050] [Table 3]

[0051] Example 5 Polishing was initiated using a silica slurry at a pH above the isoelectric potential where the particles have a negative charge, with pads without ZHP and pads with 10 wt% ZHP. The removal rate of TEOS was almost the same, and on average, it was up to 1.7 percent lower with the ZHP-containing pads compared to the ZHP-free pads. The SiN selectivity was twice as high with the ZHP-free pads as with the ZHP-containing pads. In addition, the ZHP-containing pads showed substantially higher defects (scratch and chatter).

[0052] Example 6 Polishing was initiated using a silica slurry with a pH below the isoelectric potential at which the particles have a positive charge, with pads without ZHP and pads with 10 wt% ZHP. The TEOS removal rate was more than 18 percent higher with the pad containing ZHP than with the pad without ZHP (2278 Å / min vs. 1922 Å / min).

[0053] This disclosure further includes the following aspects:

[0054] Embodiment 1: A polishing pad useful in chemical-mechanical polishing, having a polishing portion comprising a polymer base material and polishing rate-enhancing layered particles containing phosphates or arsenates of group III-A or group IV-A metals.

[0055] Embodiment 2: The polishing pad of Embodiment 1, wherein the rate-improving layered particles comprise a material having the formula M(HYO4)2n(H2O) [wherein M is a metal ion of group III-A or group IV-A, Y is P or As, preferably P, and n is 0, 1, or 2].

[0056] Embodiment 3: M is Zr +4 Ti +4 or Ce+4 A polishing pad of embodiment 2, wherein Y is P and n is 1.

[0057] Embodiment 4: A polishing pad according to any one of the preceding embodiments, wherein the rate-improving layered particles have a layered crystalline structure.

[0058] Embodiment 5: A polishing pad according to any one of the prior embodiments, wherein the rate-improving layered particles are zirconium hydrogen phosphate.

[0059] Embodiment 6: An abrasive pad according to any one of the preceding embodiments, wherein the polymer matrix comprises polyurethane, polyolefin, polyethylene, polypropylene, polyester, polyether, nylon, polyvinyl alcohol, polyvinyl acetate, polyacrylate, polycarbonate, polyacrylamide, polyamide, nylon, polyimide, polyetherketone, polysulfone, and fluoropolymers, copolymers thereof, or mixtures thereof, preferably comprising polyurethane.

[0060] Embodiment 7: A polishing pad of any one of the preceding embodiments, wherein the amount of rate-improving layered particles is at least 0.1, preferably at least 1, more preferably at least 2, even more preferably at least 3, most preferably at least 5, up to a maximum of 20, preferably up to a maximum of 15, more preferably up to a maximum of 10 weight percent, based on the total weight of the polishing portion.

[0061] Embodiment 8: An abrasive pad according to any one of the preceding embodiments, wherein the amount of rate-improving layered particles can be 0.1 to 20 volume percent, 1 to 18 volume percent, or 2 to 15 volume percent based on the total volume of the abrasive layer.

[0062] Embodiment 9: A polishing pad according to any one of the preceding embodiments, wherein the rate-improving layered particles are in the form of a plate.

[0063] Embodiment 10: A polishing pad of any one of the preceding embodiments, wherein the plate-like shape has an average dimension of at least 0.5, preferably at least 1, more preferably at least 2 microns in a direction perpendicular (or substantially perpendicular) to the thickness, and at the same time can be up to 20, preferably up to 10, more preferably up to 7, or most preferably up to 5 microns.

[0064] Embodiment 11: A polishing pad according to Embodiment 9 or 10, wherein the plate-shaped part has an aspect ratio of 3 to 20, preferably 3 to 10.

[0065] Embodiment 12: A polishing pad according to any one of the prior embodiments, wherein the polishing portion further comprises one or more micro-elements.

[0066] Embodiment 13: The polishing pad of Embodiment 12, wherein micro-elements provide porosity in the polishing area.

[0067] Embodiment 14: The polishing pad of Embodiment 13, wherein one or more microelements include hollow microelements.

[0068] Embodiment 15: The polishing pad according to Embodiment 14, wherein the amount (volume percentage) of one or more hollow micro-elements is 0 to 50, preferably 5 to 45, more preferably 10 to 35 volume percent.

[0069] Embodiment 16: A polishing pad according to Embodiment 14 or 15, wherein the micro-elements have a diameter of at least 10 microns, but have a weight-average diameter of up to 150 microns or up to 50 microns when measured by laser diffraction.

[0070] Embodiment 17: The polished portion has a viscosity of 0.4 to 1.15, preferably 0.7 to 1.0 g / cm³, when measured according to ASTM D1622 (2014). 3 A polishing pad of any of the preceding embodiments having a density of .

[0071] Embodiment 18: A polishing pad according to any of the preceding embodiments, wherein the polishing surface has a Shore D hardness of 28 to 75 when measured according to ASTM D2240 (2015).

[0072] Embodiment 19: A polishing pad according to any of the preceding embodiments, wherein the polishing portion has an average thickness of 0.5 to 4 mm, preferably 0.7 to 3 mm, more preferably 1 to 3 mm, and even more preferably 1.3 to 2.5 mm.

[0073] Embodiment 20: A polishing pad according to any of the prior embodiments, further comprising at least one additional layer in surface contact with the polishing layer.

[0074] Embodiment 21: The polishing pad of Embodiment 20, wherein at least one additional layer comprises a base layer.

[0075] Embodiment 22: A polishing pad according to Embodiment 20 or 21, wherein the base layer is adhered to the back surface of the polishing portion.

[0076] Embodiment 23. An abrasive pad according to any of Embodiments 20 to 22, wherein the base layer is pressable.

[0077] Embodiment 24: A polishing pad according to any of the preceding embodiments, wherein the volume porosity in the polishing portion can be 0 to 50, preferably 5 to 45, more preferably 10 to 35 percent.

[0078] Embodiment 25: An abrasive pad according to any of the preceding embodiments, wherein the polymer base material includes polyurethane.

[0079] Embodiment 26: A method comprising the steps of providing a substrate, providing a polishing pad according to any one of Embodiments 1 to 25, providing a slurry between the polishing pad and the substrate, and polishing the substrate using the pad and the slurry.

[0080] Embodiment 27: The method of Embodiment 26, wherein the slurry contains particles, and polishing is performed at a pH in which at least a portion of the particles have a positive charge or a positive surface charge.

[0081] Embodiment 28: The method of Embodiment 26 or 27, wherein the slurry contains cerium oxide particles.

[0082] Embodiment 29: The method of Embodiment 28, wherein the slurry contains ceria particles in an amount of at least 0.01, preferably at least 0.1, up to 20, preferably up to 10, more preferably not, or up to 5 weight percent, based on the total weight of the slurry.

[0083] Embodiment 30: Any one of Embodiments 26 to 29, wherein the slurry contains silicon dioxide particles.

[0084] Embodiment 31: Any one of Embodiments 26 to 30, wherein the polishing pad is on a platen and the pressure of the platen is 6 to 35, preferably 10 to 30 kilopascals (kPa).

[0085] Embodiment 32: The method of Embodiment 31, wherein the platen speed is 40 to 100, preferably 50 to 90 rpm.

[0086] Embodiment 33: Any one of embodiments 26 to 32, wherein the pH of the slurry during polishing is 2 to 7, preferably 2.5 to 6.8.

[0087] Compositions, methods, and articles may, by alternative means, consist of, or be essentially composed of, any suitable material, process, or component disclosed herein. Compositions, methods, and articles may, additionally or by alternative means, be formulated to lack or substantially lack any material (or type), process, or component that is not otherwise necessary for achieving the function or purpose of the composition, method, or article.

[0088] All ranges disclosed herein encompass their endpoints, which are independently combinable (for example, the range “up to 25 wt.% or more specifically, 5 wt.% to 20 wt.%” encompasses the endpoint and all intermediate values ​​of the range “5 wt.% to 25 wt.%”). Furthermore, the upper and lower limits described can be combined to form ranges (for example, “at least 1 or at least 2 weight percent” and “up to 10 or 5 weight percent” can be combined as the range “1 to 10 weight percent,” or “1 to 5 weight percent,” or “2 to 10 weight percent,” or “2 to 5 weight percent”). “Combinations” include formulations, mixtures, alloys, reaction products, etc. Terms such as “first,” “second,” etc., do not imply any order, quantity, or importance, but are used to distinguish one element from another. The terms “a,” “an,” and “the” are not limited in quantity and should be interpreted as encompassing both singular and plural forms unless otherwise indicated herein or the context clearly contradicts them. “Or” means “and / or” unless otherwise explicitly stated. Throughout this specification, references to “several embodiments,” “a particular embodiment,” etc., mean that certain elements described in relation to that embodiment are included in at least one embodiment described herein and may or may not be present in other embodiments. Furthermore, the described elements may be combined in any preferred manner in various embodiments. “That combination” is not limited and encompasses any combination that optionally includes at least one of the listed components or properties together with similar or equivalent components or properties not listed.

[0089] Unless otherwise indicated herein, all test standards are substantially the most recent standards as of the filing date of this application, or, if priority is claimed, the filing date of the earliest priority application in which the test standard appears.

Claims

1. A polishing pad useful in chemical mechanical polishing having an abrasive portion comprising a polymer matrix and layered particles for enhancing the removal rate, the layered particles comprising a phosphate or arsenate of a Group III-A or Group IV-A metal.

2. The layered particles are represented by the formula M(HYO 4 ) 2 n (H 2 O) wherein M is Zr +4 , Ti +4 Or Ce +4 2. The polishing pad of claim 1, comprising a material having the formula:

3. 10. The polishing pad of claim 1, wherein the layered particles have an alternating crystal structure that cleaves into platelets.

4. 2. The polishing pad of claim 1, wherein the layered particles are zirconium hydrogen phosphate particles.

5. 2. The polishing pad of claim 1, wherein the polymer matrix comprises polyurethane, polyolefin, polyethylene, polypropylene, polyester, polyether, nylon, polyvinyl alcohol, polyvinyl acetate, polyacrylate, polycarbonate, polyacrylamide, polyamide, polyimide, polyether ketone, polysulfone, and fluoropolymer, copolymers thereof, or mixtures thereof.

6. 10. The polishing pad of claim 1, wherein the amount of layered particles is from 1 to 20 weight percent, based on the total weight of the polishing layer.

7. 2. The polishing pad of claim 1, wherein the layered particles are in the form of plates having an average length of 0.5 to 20 microns.

8. 10. The polishing pad of claim 1 having a porosity of up to 50 volume percent.

9. 13. A method comprising the steps of: providing a substrate; providing a polishing pad according to claim 1; providing a slurry between the polishing pad and the substrate, the slurry comprising particles; and polishing the substrate with the pad and the slurry at a pH such that at least a portion of the particles in the slurry have a positive charge.

10. 10. The method of claim 9, wherein the particles comprise cerium oxide particles and the pH is less than 6.5.